Imaging performance of a CaWO4/CMOS sensor (Fracture and Structural Integrity, 2019)
The aim of this study was to investigate the modulation transfer function (MTF) and the effective gain transfer function (eGTF) of a non-destructive testing (NDT)/industrial inspection complementary metal oxide semiconductor (CMOS) sensor in conjunction with a thin calcium tungstate (CaWO4) screen. Thin screen samples, with dimensions of 2.7x3.6 cm2 and thickness of 118.9 μm, estimated from scanning electron microscopy-SEM images, were extracted from an Agfa Curix universal screen and coupled to the active area of an active pixel (APS) CMOS sensor. MTF was assessed using the slanted-edge method, following the IEC 62220-1-1:2015 method. MTF values were found high across the examined spatial frequency range. eGTF was found maximum when CaWO4 was combined with charge-coupled devices (CCD) of broadband anti-reflection (AR) coating (17.52 at 0 cycles/mm). The combination of the thin CaWO4 screen with the CMOS sensor provided very promising image resolution and adequate efficiency properties, thus could be also considered for use in CMOS based X-ray imaging devices, for various applications.
Keywords: CaWO4; Phosphors; Medical imaging; APS; CMOS sensors; MTF